THE IMPORTANCE OF IMPLEMENTING NON-CONVICTION BASED ASSET FORFEITURE IN THE RECOVERY OF CORRUPTION PROCEEDS ASSETS - Widiartana, Gregorius (CV. Lafadz Jaya, 2024)
The Anti-Corruption Convention has mandated participating countries to confiscate assets resulting from corruption without punishment. This aims to further optimize recovery of state losses due to corruption. Difficulties that may be encountered when confiscation of assets is carried out after the verdict is that the confiscation of assets fails to be carried out because the judge's decision states that the defendant is not guilty or the assets resulting from corruption have been confiscated by the defendant. This article will discuss the importance of implementing asset confiscation without punishment (or also called Non-Conviction Based Asset Forfeiture) as an effort to optimize recovery of state losses. The research method used in this writing is the normative legal research method. The approach used is a conceptual approach. The results of this research are that the Non-Conviction Based Asset Forfeiture mechanism is a form of shift from material truth regarding corrupt behavior carried out by the defendant to formal truth regarding the legality of assets controlled by the corruptor. The focus of this mechanism is not on the fault of the defendant who has committed corruption, but on the illegal assets under his control.